Rosa × damascena Herrm. essential oil: anti-tyrosinase activity and phytochemical composition - Wu, Qiuyan; Fang, Wanting; Liu, Hao; Liu, Zhong; Xu, Xuetao (Frontiers in Pharmacology, 2024)
Tyrosinase is a key enzyme in melanin synthesis, and its natural inhibitors are receiving increasing attention. Rosa × damascena Herrm. essential oil (RDEO), as important functional metabolites, was widely known due to its biological activities. But its tyrosinase inhibitory activity has not been detailed investigated. Therefore, in this paper, RDEO was comprehensively investigated the tyrosinase inhibitory, followed by the phytochemical composition analysis. Activity screening results showed that RDEO exhibited effective anti-tyrosinase activity and was a reversible and mixed-type inhibitor. CD assay results revealed that RDEO could affect the conformation of tyrosinase to reduce the activity. In B16F10 cells, RDEO (25-100 μg/mL) could inhibit intracellular tyrosinase activity and decrease melanin content. Finally, GC-MS analysis of RDEO found that citronellol (21.22%), geraniol (14.1%), eicosane (11.03%), heneicosane (6.65%) and 1nonadecene (5.16%) were its main phytochemical compositions. This study provided data support for Rosa × damascena Herrm. essential oil as one potential natural tyrosinase inhibitor and its applications in cosmetics and medicine.